High temperature crystal chemistry of the n = 3 Ruddlesden-Popper phase LaSr3Fe1.5Co1.5O10 - δ - Prado, Fernando Daniel; Abate, Anabella Angela; Caneiro, Alberto; Cuello, Gabriel Julio (Elsevier Science, 2015)
Fil: Prado, Fernando Daniel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional del Sur; Argentina